Johann Sebastian Bach: The Learned Musician - Wolff, Christoph 1940- (Oxford Oxford University Press, 2002)
Finalist for the 2001 Pulitzer Prize in Biography. A landmark biography of Bach on the 250th anniversary of the composer's death, written by the leading Bach scholar of our age.Although we have heard the music of J. S. Bach in countless performances and recordings, the composer himself still comes across only as an enigmatic figure in a single familiar portrait. As we mark the 250th anniversary of Bach's death, author Christoph Wolff presents a new picture that brings to life this towering figure of the Baroque era. This engaging new biography portrays Bach as the living, breathing, and sometimes imperfect human being that he was, while bringing to bear all the advances of the last half-century of Bach scholarship. Wolff demonstrates the intimate connection between the composer's life and his music, showing how Bach's superb inventiveness pervaded his career as musician, composer, performer, scholar, and teacher. And throughout, we see Bach in the broader context of his time: its institutions, traditions, and influences. With this highly readable book, Wolff sets a new standard for Bach biography. "A monumental work that must find its way into the library of every musician and every dedicated lover of music."?Isaac Stern "It's unlikely that anyone will fashion a finer tribute to [Bach's] genius."?Los Angeles Times Book Review "A magisterial biographical portrait...necessarily learned, but also user-friendly, helpful and entertainingly informative."?Chicago Tribune"Likely to be the standard one-volume Bach biography for some time to come."?New York Review of Books "A work of clarity worthy of its subject and his music."?Wall Street Journal
Keywords: Bach, Johann Sebastian -- 1685-1750; 17th Century (1601-1700); 18th Century (1701-1800); Composer; Biography; Germany